Janice VanCleave's math for every kid : easy activities that make learning math fun - VanCleave, Janice Pratt; Clark, Barbara (New York : J. Wiley, 1991)
Presents 101 simple math problems and experiments intended to introduce basic mathematical principles.
Includes index.
Spine title: Math for every kid.
Elem. School Library Collection.
School Library Journal.
6.2.
6.2
Keywords: Mathematics -- Juvenile literature; Mathematics; Mathematics